DINAMIKA AGRESIVITAS PADA ISTRI YANG MENJADI KORBAN JUGA PELAKU KEKERASAN DALAM RUMAH TANGGA - , Orley Charity Sualang, Prof. Dr. Sofia Retnowati, MS., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Domestic Violence has become a phenomenon which cause the victims to family members. This far, the intervention of domestic violence canât be solved optimally, this thing is proven from increase sum of case over the years and the existence of psychological tension which experienced by wife in consequence of husband violence so that cause frustration. There are some type of negative mechanism of frustration such as aggression behavior which shown by a desire to releasing feel of anger or a cluster of vexation on oneâs side which weaker and closest that is children. This study aims to describe and explore aggressivity dynamic of wives who become victims also perpetrators of domestic violence. This study using qualitative methods with indepth focused interview were used to acquire data from two informants which as a wife or divorce mother (20-40 years old) and become victims from her husband also perpetrators to her son or daughters. From the discussion of the interview was concluded that the dynamics of aggressiveness in wives who are victims of domestic violence perpetrators can also be seen from the aggressor stimulus or the stressor. Aggressors stimulus or stressors is sustained by the wife in the form of positive coping (problemfocused coping, and spirituality) and negative coping (stress, focus on the withdrawal and confrontation, and aggressive behavior in children). Postive coping should be done effectively, but the reality is not because wife is stressed so the behavior does not appear positive coping, but negative coping. If wife can make a positive coping effectively, then it can resolve the conflict and domestic violence because she has a positive mental health and psychological well-being (such as: self-acceptance, potential selfdevelopment, positive relationships with others, the ability to regulate behavior, has a purpose of life, and the ability to choose the environment that are useful to achieve the goal). However, if the wife is not able to cope her stress, then she can be an aggressor to her children and she has a tendency suffered emotionally unstable personality disorder, borderline type and post-traumatic stress disorder.